When Safety Meets the Economy: Mapping Fifty Years of Research on Agricultural Labor, Occupational Health, and Economic Outcomes - Qalbin Salim Fazli; Mussa Issack Delya; Erick Hironimus Kihwili; Ghalieb Mutig Idroes; Dimas Bagus Wiranatakusuma; Ghazi Mauer Idroes (Grimsa Journal of Business and Economics Studies, 2026)
Research on occupational safety in agriculture has expanded substantially over the past decades, yet its economic dimensions remain dispersed across multiple disciplinary traditions. This study aims to map the intellectual structure and thematic development of scholarly work linking agricultural labor, occupational health, and economic outcomes. Using a bibliometric approach, publications indexed in the Scopus database were systematically analyzed covering the period from 1973 to 2026. A total of 1229 peer reviewed articles and reviews were examined using bibliometrix in R and VOSviewer to identify publication trends, influential sources, leading contributors, country collaborations, keyword networks, and thematic patterns. The results reveal a sustained growth in research output, particularly after the mid-2000s, alongside a multidisciplinary publication landscape dominated by environmental, health, and agricultural economics journals. Keyword co-occurrence and thematic analyses indicate that while occupational safety and health constitute a central research focus, economic themes such as productivity, labor, income, sustainability, and policy are increasingly integrated but remain distributed across distinct clusters. This bibliometric evidence highlights the evolving recognition of occupational safety as an economic issue within agricultural systems. The study contributes by consolidating fragmented research streams into a coherent overview, offering insights for economists, policymakers, and researchers interested in labor welfare, productivity, and sustainable agricultural development.